Relationship Between Blood-borne Parameters and Gross Lesions in Leishmania chagasi Seroreagents Dogs - Viadanna, Pedro H. O.; Medeiros, Alessandra A.; Szabó, Matias J. P.; Mundim, Antonio V.; Soares, Nicolle P.; Limongi, Jean E.; Paula, Márcia B. C. (Brazilian Journal of Veterinary Pathology, 2011)
Canine visceral leishmaniasis, a systemic and chronic zoonosis, is caused in Brazil by the protozoan Leishmania chagasi, a widely accepted synonym for Leishmania infantum. The agent and disease has recently arrived in Uberlândia city, Minas Gerais, Brazil. In this research, hematological parameters and gross lesions of dogs with visceral leishmaniasis were compared, to highlight aspects of disease in a recent outbreak. For this purpose forty mongrel dogs from Uberlândia seroreagents by ELISA and RIFI tests were selected. Animals were categorized as asymptomatic,(AS); oligosympytomatic (OS) and symptomatic (SS). Blood samples were collected and dogs were euthanized according to Brazilian Federal rules. Animals were then submitted to standard necropsy procedures at Veterinary Pathology sector of the Federal University of Uberlândia. Most prominent alterations were of observed in respiratory and integumentary systems, with pilose rarefaction (OS: 41.7%, SS: 60.1%), specially periocular (OS: 25.0 %, SS: 26.1%) and thoracic/pelvic members (OS: 25.0%, SS: 30.4%). Onychogryphosis (OS: 41.7%, SS: 39.1%), pulmonar edema (OS: 25.0%, SS: 39.1%), and congestion (OS: 41.7%, SS: 60.9%). Moreover animals displayed increase of several organs; liver (67.5%), spleen (60%), lymph nodes (72.5%) and kidney (47.5%). Hematological alterations included low red cell counts and decreased hemoglobin content. Overall, 27.5% of animals presented leukocitosis, 52.5 % of dogs had increased band neutrophil counts 5.0 % had basophilia and 42.5% monocytopenia. No correlations was found between hematological findings and clinical status of animals (asymptomatic, oligosymptomatic or symptomatic). Presumptively, we can conclude that, in asymptomatic animals there are hematological as well as gross alterations.